2020
DOI: 10.3390/atmos11111252
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Comparison of Gauge-Based Gridded Data, Reanalysis and Satellite Precipitation Product with an Emphasis on Hydrological Modeling

Abstract: Precipitation is essential for modeling the hydrologic behavior of watersheds. There exist multiple precipitation products of different sources and precision. We evaluate the influence of different precipitation product on model parameters and streamflow predictive uncertainty using a soil water assessment tool (SWAT) model for a forest dominated catchment in India. We used IMD (gridded rainfall dataset), TRMM (satellite product), bias-corrected TRMM (corrected satellite product) and NCEP-CFSR (reanalysis data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…It also includes output components that allow for the analysis of various water-related systems in watersheds. Recent studies have used the SWAT model to evaluate the consequences of changing the climate on streamflow and sediment load [22,29,30]. For example, Mohseni et al (2023) [18] used the SWAT model to evaluate the impact of climate change and land use change on streamflow over the Parvara Mula Basin, India.…”
Section: Introductionmentioning
confidence: 99%
“…It also includes output components that allow for the analysis of various water-related systems in watersheds. Recent studies have used the SWAT model to evaluate the consequences of changing the climate on streamflow and sediment load [22,29,30]. For example, Mohseni et al (2023) [18] used the SWAT model to evaluate the impact of climate change and land use change on streamflow over the Parvara Mula Basin, India.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using various statistical metrics, hydrological modeling has been increasingly utilized to compare the accuracy of SPPs and assess the performance of various bias correction methods [33][34][35]. In the Kashgar catchment in Xinjiang, China, [36] utilized daily SPPs, such as GSMaP, CHIRPS (Climate Hazards Group InfraRed Preconception with Station Data), 3B42, and SM2RAIN (Rainfall Estimation from Soil Moisture Observations), as rainfall inputs to establish hydrological SWAT (Soil and Water Assessment Tool) models.…”
Section: Introductionmentioning
confidence: 99%
“…Roti et al [31] reviewed the applicability of physically distributed models and concluded that the SWAT model outperformed AGNPS, ANSWERS and WEPP models [32,33] in both small and large areas [34]. Furthermore, with spatiotemporal variability of the hydrological process, SWAT produces acceptable results all over the world [35][36][37][38][39][40][41]. The majority of the recent studies used SWAT in conjunction with a geographical information system (GIS) interface for a variety of purposes, including modeling of runoff, soil moisture, sediment and water balance [19,21,[42][43][44], climate change [45] and identifying critical source areas and evaluation of best management practices (BMPs) for sediments and nutrients [20,33,46] across the world.…”
Section: Introductionmentioning
confidence: 99%
“…The Nagavali and Vamsadhara river basins in India are vulnerable to frequent floods [11,39,47,48]. These basins are mainly dominated by agricultural activities and forest cover, which provide a livelihood for farmers in the Odisha districts of Kalahandi, Koraput and Rayagada, as well as the Andhra Pradesh districts of Srikakulam and Vizianagaram.…”
Section: Introductionmentioning
confidence: 99%